A study of knowledge and self care practices in patients of type 2 diabetes mellitus - Praveen Govinda Gowda; Vittal Balakrishna Ganjigatte (Electronic Physician, 2012)
Background: India is harbouring the largest number of diabetic patients in the world. Poor knowledge and practices are some of the important factors influencing the development and progression of diabetes and its complications, which are easily preventable. Though self care constitutes 95% of diabetes management it is not given due emphasis. This study was undertaken to assess the knowledge and self-care practices in type 2 diabetes mellitus.